INTACT '10 - M.H. Abd Halim Mohd Hussin;; A. Zainol Abidin (Universiti Sains Islam Malaysia, 2024)
INTACT '10 is a training module developed from a research base outcome. INTACT '10 is a training module that fulfills the need of training and effort in preparing professional helpers in the treatment and rehabilitation. INTACT '10 consist of 3 major concepts interrelated and integrated as a powerful tool to enhance competency of counselors. Counselor's competency, self efficacy and Islamic Spirituality stand as major components of the module. INTACT '10 innovatively designed SELF-RATING OF ADDICTION COUNSELING COMPETENCY (SRACC) and SELF RATING ISLAMIC RELIGIOSITY SCALE (SRIRS) slf administered instruments to be used as psychometric for counselors and professionals working with addicts. INTACT '10 are anticipated as a product that can enhance self-awareness for counselors and professionals' helpers in helping them achieve optimum performance.